Beyond Okun's Law: Output Growth and Labor Market Flows - Guay C. Lim; Robert J. Dixon; Jan C. van Ours (Tinbergen Institute, 2018)
This paper studies the relationship between the change in the unemployment rate and output growth using an approach based on labor market flows. The framework shows why the Okun coefficient may be constant/time-varying and/or symmetric/asymmetric and that the outcome lies with the behavior of the labor flows in response to growth. The encompassing framework nests the conditions to determine the properties of the Okun coefficient without the need to rely on retrospective arbitrary dating of recessions. The framework also highlights the potential misspecification in conventional models of Okun's Law unless stringent conditions are assumed about the behavior of labor flows. The empirical analysis is based on the stock-consistent labor market flows data developed by the BLS for the period 1990:2-2017:3.
Keywords: E24; E32; J21; 330; Labor flows; Time-varying Okun; Asymmetry